Sistem Pertanian Konservasi Pola Agroforestri dan Hubungannya dengan Tingkat Erosi di Wilayah Sub-DAS Wuno, Das Palu, Sulawesi Tengah - Naharuddin Naharuddin (Department of Urban and Regional Planning, Diponegoro University, 2018)
The upstream part of Wuno Subwatershed in Palu Watershed experiences massive land use change exploitation, causing erosion impact increasingly. An alternative way for reduce the erosion level is by applying conservation farming system. This research aims to examine the conservation farming system with GIS-based agroforestry pattern and its effects to the erosion level reduction perceived by the community living in the Wuno Subwatershed. The method used is image interpretation and field survey to obtain data directly on an object using GPS.The results show that there are four agroforestry patterns in Wuno subwatershed, that is, trees along border, alternate rows, alley cropping and random mixture. The highest erosion level shown by the alley cropping pattern at 5.17 grams/ha and the lowest is trees along border at 0.47 grams/ha, all compared to the total rainfall level of 493.6 mm. The canopy cover of the agroforestry pattern influences the erosion level occurs.